Samuel Hay Kauffmann papers - Kauffmann, Samuel Hay, 1829-1906.
Correspondence, writings, reports, research notes, clippings, and other papers relating chiefly to Kauffman's research on equestrian statues. Includes drafts of an address delivered before the Literary Society of Washington (Washington, D.C.). Correspondents include Joseph Alexis Bailly, Truman Howe Bartlett, Sir Joseph Edgar Boehm, and the Benj. French & Co., Boston, Mass.
Newspaperman, art historian, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bailly, Joseph Alexis, -- 1825-1883 -- Correspondence; Bartlett, Truman Howe, -- 1835-1923 -- Correspondence; Boehm, Joseph Edgar, -- Sir, -- 1834-1890 -- Correspondence; Benj. French & Co. -- Correspondence; Literary Society of Washington (Washington, D.C.); Equestrian statues; Art historians; Authors; Newspapermen